Znaczenie efektu Cantillona w teorii ekonomii - Sieroń, Arkadiusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The aim of this article is to examine the role of the Cantillon effect in economics. The literatureof economic theory lacks the detailed discussion of the implications of the first-round effect foreconomics. This paper attempts to fill this gap. The article is mainly theoretical, but considerationspresented are illustrated by relevant empirical data. Based on the analysis, the author concludes that the effect of Cantillon develops particularly the theory of money and inflation, the theory of bankingand central banking, the theory of business cycle and price bubbles, the theory of income distribution and income and wealth inequalities, and the theory of public choice
Keywords: efekt Cantillona; teoria pieniądza; inflacja; teoria bankowości; bankowość centralna; teoria cykli koniunkturalnych i baniek cenowych; teoria dystrybucji dochodu i nierówności dochodowych; teoria wyboru publicznego